Combining distance and force measurements to monitor the usage of walker assistive devices - Pereira, José Miguel Costa Dias (2017)
Trabalho apresentado na IEEE - International Instrumentation and Measurement Technology Conference, 22-25 maio de 2017, Turim, Itália